Modernization of the Power Supply System Applying Solar Cells and Batteries - Serdiuk, Tetiana M.; Serchenko, Maksym; Radkevych, Anatolii V.; Serdiuk, Svitlana; Skalko, Viktor (MATEC Web of Conferences, 2024)
ENG: In this paper, an assessment was made of the installation of solar panels as a backup power source for the Post of electric centralization. The advantages of using this system and an example of calculations for the Post of electric centralization were given. The norms of electricity consumption were analyzed.
Т. Serdiuk: ORCID 0000-0002-2609-4071; M. Serchenko: 0009-0007-7076-6211; A. Radkevych: ORCID 0000-0001-6325-8517
Keywords: power supply system; modernization; solar cells and batteries; КАТ; TECHNOLOGY; TECHNOLOGY::Electrical engineering, electronics and photonics